2009
DOI: 10.1136/hrt.2009.170241
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of procollagen type III N-terminal amino peptide in patients with congenital heart disease

Abstract: The increased serum PIIIP levels in proportion to the severity of ventricular load or cyanosis suggest enhanced myocardial synthesis of collagen type III in patients with CHD. Suppression of the PIIIP level by ACEI suggests the involvement of the renin-angiotensin-aldosterone system in myocardial fibrosis. These data provide the basis for the development of new diagnostic and therapeutic strategies in patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…[22] In a previous study by our group, the PIIIP level was found to be elevated owing to various hemodynamics in children with CHD. [23] In children with VSDs or ASDs exhibiting ventricular volume overload, the PIIIP level was found to correlate with the pulmonary-to-systemic blood flow ratio (Qp/Qs), whereas in children with Tetralogy of Fallot (TOF), the PIIIP level was found to correlate with the degree of cyanosis. Moreover, we also found that the PIIIP levels were inhibited by angiotensin-converting enzyme inhibitors.…”
Section: Biomarker Of Myocardial Fi Brosis and Interstitial Remodelinmentioning
confidence: 97%
“…[22] In a previous study by our group, the PIIIP level was found to be elevated owing to various hemodynamics in children with CHD. [23] In children with VSDs or ASDs exhibiting ventricular volume overload, the PIIIP level was found to correlate with the pulmonary-to-systemic blood flow ratio (Qp/Qs), whereas in children with Tetralogy of Fallot (TOF), the PIIIP level was found to correlate with the degree of cyanosis. Moreover, we also found that the PIIIP levels were inhibited by angiotensin-converting enzyme inhibitors.…”
Section: Biomarker Of Myocardial Fi Brosis and Interstitial Remodelinmentioning
confidence: 97%
“…43 Myocardial cells are finally differentiated cells and do not have the potential to divide. In addition, the reproduction of myocardial cells from stem cells and progenitor cells is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…AUROC, area under the receiver operating characteristic curve; CHB, chronic hepatitis B. AUROC of the noninvasive model >0.800 (in bold) 37. and its serum levels are elevated in various pathologic disorders, such as viral and nonviral liver disease,38 congenital heart disease,39 chronic kidney disease40 and systemic sclerosis 41. Many noninvasive models for assessing liver fibrosis obtained commendable performance by combining PIIINP and other serum markers 27,38.…”
mentioning
confidence: 99%